Expansive arterial remodeling of the carotid arteries and its effect on atherosclerotic plaque composition and vulnerability: an in-vivo black-blood 3T CMR study in symptomatic stroke patients. Issue 1 (December 2016) - Saam, Tobias; Habs, Maximilian; Buchholz, Martin; Schindler, Andreas; Bayer-Karpinska, Anna; Cyran, Clemens; Yuan, Chun; Reiser, Maximilian; Helck, Andreas
Abstract Background Based on intravascular ultrasound of the coronary arteries expansive arterial remodeling is supposed to be a feature of the vulnerable atheroslerotic plaque. However, till now little is known regarding the clinical impact of expansive remodeling of carotid lesions. Therefore, we sought to evaluate the correlation of expansive arterial remodeling of the carotid arteries with atherosclerotic plaque composition and vulnerability using in-vivo Cardiovascular Magnetic Resonance (CMR). Methods One hundred eleven symptomatic patients (74 male/71.8 ± 10.3y) with acute unilateral ischemic stroke and carotid plaques of at least 2 mm thickness were included. All patients received a dedicated multi-sequence black-blood carotid CMR (3Tesla) of the proximal internal carotid arteries (ICA). Measurements of lumen, wall, outer wall, hemorrhage, calcification and necrotic core were determined. Each vessel-segment was classified according to American Heart Association (AHA) criteria for vulnerable plaque. A modified remodeling index (mRI) was established by dividing the average outer vessel area of the ICA segments by the lumen area measured on TOF images in a not affected reference segment at the distal ipsilateral ICA. Correlations of mRI and clinical symptoms as well as plaque morphology/vessel dimensions were evaluated. Results Seventy-eight percent (157/202) of all internal carotid arteries showed atherosclerotic disease with AHA Lesion-Type (LT) III or higher. The mRI of the ICA was significantly different in normal artery segments (AHA LT I; mRI 1.9) compared to atherosclerotic segments (AHA LT III-VII; mRI 2.5;p  < 0.0001). Between AHA LT III-VII there was no significant difference of mRI. Significant correlations (p  < 0.05) of the mRI with lumen-area (LA), wall-area (WA), vessel-area (VA) and wall-thickness (WT), necrotic-core area (NC), and ulcer-area were observed. With respect to clinical presentation (symptomatic/asymptomatic side) and luminal narrowing (stenotic/non-stenotic) no relevant correlations or significant differences regarding the mRI were found. Conclusion Expansive arterial remodeling exists in the ICA. However, no significant association between expansive arterial remodeling, stroke symptoms, complicated AHA VI plaque, and luminal stenosis could be established. Hence, results of our study suggest that expansive arterial remodeling is not a very practical marker for plaque vulnerability in the carotid arteries.